Strengthening Teacher Competence Through The Integration of Deep Learning Models and Galatama Activities at MAN Insan Cendekia Halmahera Barat - Adiyana Adam; Kamarun M. Sebe; Azis Los’en; Hamzah Umasugi; Mardiani Masuku; Suhaiba Raudah Umasangaji (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This community service program aims to enhance teachers’ pedagogical, collaborative, and reflective competencies through the integration of the Deep Learning model and Galatama activities at MAN Insan Cendekia Halmahera Barat. The program employed the Participatory Action Research (PAR) approach, which consists of four stages: planning, acting, observing, and reflecting. Twenty subject teachers actively participated in the three-day workshop that included needs analysis, adaptive lesson plan design, and peer reflection sessions through Galatama. The results revealed significant improvement: 85% of teachers understood the concept of Deep Learning, 90% were able to design HOTS-based learning activities, and 95% reported increased confidence in classroom implementation. The program also fostered a reflective and collaborative culture among teachers while strengthening the spiritual and social values that characterize madrasah education. Therefore, the integration of Deep Learning and Galatama proved effective in shaping teachers as reflective practitioners in the era of digital educational transformation.